Reduction of contamination in oil refining - Legua Cárdenas, José (2001)
The present work is an effort to achieve an industrial eco-efficiency reducing the direct and indirect environmental impacts present in the industrial refining of soybean oil, the use of the neutralizing agent of potassium hydroxide is proposed instead of what is currently being used, which is sodium hydroxide, and in this way eliminate the liquid tributary that is poured into the public network causing a negative environmental impact on the water bodies and the sewer system; This adverse situation for the environment will revert into something favorable for the ecosystem. For this, a physicochemical treatment will be given to the tributary, transforming it into a liquid fertilizer that can be used to provide nutrients to the cultivated soils; Other environmental advantages that would be achieved are the following: a better quality soybean oil for edible use when leaving this refining stage and using less quantity of treated water, less quantity of acid-activated clay in the bleaching of the oil, so it would have less solid waste that is dumped into the environment; therefore reducing the costs of production of refined oil by the proposed method.